Conformational signatures induced by ubiquitin modification in the amyloid-forming tau repeat domain - Giovanna Viola; Daniele Trivellato; Mikko Laitaoja; Janne Jänis; Isabella C. Felli; Mariapina D’Onofrio; Luca Mollica; Gabriele Giachin; Michael Assfalg (Proceedings of the National Academy of Sciences, 2025)
Posttranslational modifications can critically affect conformational changes of amyloid-forming proteins. Ubiquitination of the microtubule-associated tau protein, an intrinsically disordered biomolecule, has been proposed to influence the formation of filamentous deposits in neurodegenerative conditions. Given the reported link between aggregation propensity and intrinsic structural preferences (e.g., transient extended structural motifs or tertiary contacts) in disordered proteins, we sought to explore the conformational landscape of ubiquitinated tau. Exploiting selective conjugation reactions, we produced single- and double-monoubiquitinated protein samples. Next, we examined the ubiquitinated species from different standpoints using NMR spectroscopy, small-angle X-ray scattering experiments, and native ion mobility–mass spectrometry (IM–MS). Moreover, we obtained atomistic representations of the conformational ensembles via scaled MD calculations, consistent with the experimental data. Modifying the repeat domain of tau with ubiquitin had a limited effect on secondary structure propensities and local mobility of distal regions. Instead, ubiquitination enhanced the compaction of the conformational ensemble, with the effect modulated by the site and the number of modifications. Native IM–MS patterns pinpointed similarities and differences between distinct tau proteoforms. It emerges that ubiquitination exerts a position-specific influence on the conformational distribution of tau molecules. This study reveals the unique conformational features of ubiquitinated forms of tau and points to their potential impact on aggregation and phase separation propensities, offering clues for a better understanding of disease-related structural alterations.